1998
DOI: 10.1111/j.1600-0633.1998.tb00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk from piscivorous fish influencing the diel use of macrophytes by planktivorous fish in experimental ponds

Abstract: Abstract— This study investigated interactions between zooplanktivores (roach and perch) and piscivorcs (pike and large perch) in experimental ponds (16 m2) with open water habitat and three densities of natural macrophytes. Fish habitat selection was determined both day and night and was supported by daytime observations to study anti‐predator behavioural patterns. Diel migration out from among macrophytes was seen in the absence of predators, particularly for roach, which changed from 13% of individuals bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 53 publications
6
60
0
2
Order By: Relevance
“…This may be indicated by the decreased specific consumption rates in perch after the pikeperch stocking and is in accordance with other studies in which juvenile northern pike was found to be the more effective forager compared with perch in complex littoral structures (Jacobsen and Perrow 1998). Furthermore, only the northern pike growth rates increased in experiments when northern pike only treatments were contrasted with treatments in which perch and northern pike co-occurred.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This may be indicated by the decreased specific consumption rates in perch after the pikeperch stocking and is in accordance with other studies in which juvenile northern pike was found to be the more effective forager compared with perch in complex littoral structures (Jacobsen and Perrow 1998). Furthermore, only the northern pike growth rates increased in experiments when northern pike only treatments were contrasted with treatments in which perch and northern pike co-occurred.…”
Section: Discussionsupporting
confidence: 80%
“…Intraguild predation and cannibalism are frequent interactions, among others, that may dampen the expected direct density effects on the prey populations (Polis et al 1989;Arim and Marquet 2004;Claessen et al 2004). Furthermore, the response of the predators may be additionally influenced by both densitydependent and trait-mediated responses in the prey fish communities (Brabrand and Faafeng 1993;Christensen and Persson 1993;Jacobsen and Perrow 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Abrahams and Kattenfeld (1997) hypothesized that in turbid systems, antipredator behaviour of the prey will become ineffective and will occur less frequently. Several studies found support for this hypothesis in fish-fish predatorprey systems (Abrahams and Kattenfeld 1997;Jacobsen and Perrow 1998;Jacobsen et al 2004). From this hypothesis, Abrahams and Kattenfeld (1997) derived a second hypothesis that predator-prey interactions in turbid water will be primarily characterized by the direct effects of predator consumption of prey, while in clear-water systems, direct as well as indirect effects of the predator on the prey's growth rate through behavioural modification will be important.…”
Section: Introductionmentioning
confidence: 95%
“…In shallow temperate lakes, these plants can influence the spatial distribution of fish (Tatrái and Herzig, 1995;Jacobsen and Perrow, 1998;Schindler, 1999), zooplankton (Timms and Moss, 1984;Lauridsen and Buenk, 1996), and phytoplankton (van Donk and van de Bund, 2001). The clear water state and the turbid water state are the two distinct trophic conditions known in shallow temperate lakes based on the alternative stable states hypothesis (Scheffer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Submerged vegetation can support the clear water state by decreasing nutrient availability and/or releasing allelopathic substances (bottom-up control) (van Donk and van de Bund, 2001), and providing refuges for zooplankton grazers (topdown control) (Scheffer et al, 1993). It can also provide a daytime refuge for large-bodied zooplankton, such as Daphnia (Timms and Moss, 1984;Lauridsen and Buenk, 1996;Lauridsen and Lodge, 1996;Burks et al, 2002) and has an effect on the spatial distribution of fishes (Tatrái and Herzig, 1995;Jacobsen and Perrow, 1998;Schindler, 1999) causing cascade effects in littoral area or open water. Tropical and subtropical lakes are different from temperate lakes in general characteristics of the food webs.…”
Section: Introductionmentioning
confidence: 99%